Penguatan Pendidikan Karakter Siswa melalui Pendekatan Sosiolinguistik Berbasis Budaya Lokal - Indramini Indramini (Prodi PGSD Unsultra, 2026)
Character education is a key focus in education because it plays a crucial role in shaping students' personalities and behavior. However, developments in globalization and technology have led to a shift in cultural values ​​among students, necessitating a learning approach that integrates local cultural values ​​into the educational process. This study aims to analyze the role of a local culture-based sociolinguistic approach in strengthening students' character education. The study employed a literature review method, analyzing various scientific articles, national journals, and relevant literature sources related to sociolinguistics, local culture, and character education. Data collection techniques included identifying, selecting, and analyzing literature published in the last ten years. The study's findings indicate that a local culture-based sociolinguistic approach can strengthen students' character education through the use of regional languages, oral traditions, local wisdom, sociocultural interactions, and contextual learning. This approach helps students understand the values ​​of courtesy, responsibility, cooperation, tolerance, and respect for their own culture. Furthermore, the use of local culture in learning also increases student engagement and creates a more meaningful learning process. Therefore, a local culture-based sociolinguistic approach can be a relevant alternative character education strategy for implementation in schools, particularly at the elementary school level. This research is expected to serve as a reference for developing culture- and character-based learning in educational settings.